Theoretical Foundations, Methods, and Algorithms for Lossless-in-Sense Text Compression - Emelyanov, G. M.; Mikhaylov, D. V. (Pattern recognition and image analysis, 2023)
The article is devoted to the scientific school developed by the first author in 1995–2012 in Yaroslav-the-Wise Novgorod State University (Veliky Novgorod, Russia). The finite practical goal of the research carried out by the school can be denoted here as the revelation of the most rational variant for sense transfer in a knowledge unit defined by a set of semantically equivalent natural-language phrases. One phrase here corresponds to the simple spread natural-language sentence (according to the “Meaning–Text” theory terminology). Knowledge formed herewith about synonymy and forms of language expression of relationships between concepts of some topical area are in demand in tasks requiring the establishment of full or partial equivalence in the meaning of both complete sentences of natural language and their combinations, and individual fragments of phrases. The results are both theoretical and practical in nature. Offered methods and their software implementations can be used for decision of a wide range of tasks of recognition and analysis of semantics of complex information objects (texts and images at first), and for lossless-in-sense information compression.